PENGEMBANGAN LAYANAN PEMANTAU ANAK BERBASIS LOKASI PADA PERANGKAT ANDROID - Cecilia, Cecilia; Setiadi, Arif (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2023)
These day technology develops rapidly. This matter affect the techonology utilization in many aspect today, especially when adults, teenagers and children were using Andoid smartphone. For some parents, it’s hard to spare a little time for their family and their children. This matter cause parent’s to less-care about their children and not be able to monitor their children’s activity, moreover some of this children could be in a place which they should not visit. 85% respondents from public who had married, need a monitoring service to know their children location. In nowadays, this monitoring services have already been design, however there is always some difficulty in using this kind of services because of the only language that available was english, and moreover the server was build and located overseas. This research was intended to create an monitoring sevice application based on location on Android devices that available in Indonesian to be used by parents. This application use GPS feature, Geofencing, and Google Maps that available on Android Devices.